2008
DOI: 10.1007/s00401-008-0456-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased TDP-43 protein in cerebrospinal fluid of patients with amyotrophic lateral sclerosis

Abstract: There is mounting pathological, biochemical and genetic evidence that the metabolism and aggregation of the 43-kDa transactive response (TAR)-DNA-binding protein (TDP-43) play a crucial role in the pathogenesis of sporadic and some forms of familial amyotrophic lateral sclerosis (ALS). Recently, it was reported using an ELISA system that elevated levels of TDP-43 were detected in plasma samples from patients with Alzheimer's disease and frontotemporal dementia, compared to healthy controls. To determine whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
122
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(134 citation statements)
references
References 34 publications
9
122
1
2
Order By: Relevance
“…In postmortem studies, TDP-43 inclusions are detected in approximately 97% of patients with ALS. Based on these findings, investigators have pursued TDP-43 as a biofluid biomarker for ALS [92][93][94][95]. If changes can be reliably detected in blood or CSF, TDP-43 could be a valuable biomarker for the majority of patients with ALS.…”
Section: Tar Dna-binding Protein Of 43 Kdamentioning
confidence: 99%
See 1 more Smart Citation
“…In postmortem studies, TDP-43 inclusions are detected in approximately 97% of patients with ALS. Based on these findings, investigators have pursued TDP-43 as a biofluid biomarker for ALS [92][93][94][95]. If changes can be reliably detected in blood or CSF, TDP-43 could be a valuable biomarker for the majority of patients with ALS.…”
Section: Tar Dna-binding Protein Of 43 Kdamentioning
confidence: 99%
“…Overall, these studies identified increased levels of TDP-43 in CSF from patients with ALS compared with a variety of neurologically diseased and nondiseased controls. Additionally, increased TDP-43 levels were also observed among patients who were examined within 10 months of disease onset, suggesting that TDP-43 might be useful as a prognostic indicator for early stages of ALS [93]. However, the absolute levels of TDP-43 measured in CSF varies across the studies, suggesting that the TDP-43 immunoassays are inconsistent for measuring the protein within CSF or blood samples.…”
Section: Tar Dna-binding Protein Of 43 Kdamentioning
confidence: 99%
“…Our studies focus on TDP-43 as a biological marker in CSF. As TDP-43 is mainly found in sporadic ALS cases and signifi cantly higher levels of TDP-43 are found in their CSF when compared with age-matched controls [44] , we decided to investigate these patients in a proof-of-principle type of manner, as here the neuropathology can be easier predicted compared with the other diagnosis of the FTLD spectrum, especially the bvFTD cases [37] . This included FTLD, FTLD + ALS and ALS cases.…”
Section: Other Neurochemical Markers For the Diagnosis Of Ftldmentioning
confidence: 99%
“…Prior to the current study, only TDP-43 itself has been examined as a potential biomarker for nonfamilial cases of FTLD-TDP. 11,22 One study showed elevated plasma TDP-43 levels in 46% of clinical FTD cases and 22% of clinical AD cases, but the lack of pathologic confirmation in these groups limited confident interpretation of results.…”
Section: Figure 1 Box Plots Showing Median Values Quartiles and Outmentioning
confidence: 99%